Draft genome of a clinical Pseudomonas qingdaonensis isolate from a hospitalized patient at Kenyatta National Hospital, Kenya [version 1; peer review: 2 approved] - Racheal Gachogo; Brian Ogoti; Frank Onyambu (F1000Research, 2022)
The first draft genome of Pseudomonas qingdaonensis, a gram-negative bacteria isolated from hospitalized patients in Kenya, is presented in this study. The genome was assembled using nanopore MinION readings, yielding an assembly of 8,857,650 base pairs made up of 5(five) contigs. The genome sequence of Pseudomonas qingdaonensis will help researchers better grasp its genetics. Furthermore, the data can be a valuable resource for comparative genomics and future research in this novel species.